The relationship between information technology (IT) resources and employees job perfomance at Syarikat Air Johor Holding (SAJH) / Aini Fariza Asfa Asaari - Asfa Asaari, Aini Fariza (Faculty of Business and Management, 2014)
This study is to determine the significant relationship of IT Resources to employee job performance in SAJ Holding Sdn. Bhd. Kluang Agency Office.The paper examined the significant relationship of IT Resource, which are IT Application, IT Infrastructure and IT Knowledge to the employee job performance in SAJH Kluang Agency Office.This study used samples by way of distributing questionaire using Likert Scale format questions in gathering information from respondents who are employees of SAHJ Kluang Agency Office.The finding of this study revealed that there is positive significant relationship between IT Resources and employee job performance.